Can European Union contract staff posted to a third country be divorced in a member State? And what about diplomats (ECJR of 1 August of 2022 )? - Calvo Babío, Flora (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This commentary analyses criteria for international jurisdiction in matters of divorce and divorce-related measures when Community nationals from different Member States reside with their children in third States where access to justice is not guaranteed. European Regulation rules do not provide adequate solutions when the marriage is composed of EU binationals and this is likely to infringe the right to effective judicial protection of EU nationals. This problem is linked to diplomatic status, whatever its scope, and as it affects those who enjoy it as well as those who sue a person covered by it.
Keywords: International jurisdiction; diplomatic; diplomatic status; immunity; residual jurisdiction; habitual residence; forum necessitatis; reasonable proximity